A PROSPECTIVE STUDY ON VITAMIN D DEFICIENCY AND ITS ASSOCIATION WITH THE DEVELOPMENT OF PREECLAMPSIA IN PRIMIGRAVIDA IN A TERTIARY CARE HOSPITAL - Dr. P. S. V. Mohana; Dr. G. Prameela Devi; Dr. T. Prathibha Sravanthi (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
BACKGROUND: Hypertension represents the most common medical complication of pregnancy affecting around 10% women. It is a dominant cause of maternal and perinatal morbidity. Abnormal placentation and impaired trophoblastic invasion are the triggering factors [1]. Vitamin D has immunomodulatory property on placental tissue and its deficiency plays an important role in preeclampsia pathogenesis. Objective of the study is to find the association between the deficiency of Vitamin D and preeclampsia development in primigravida.METHODOLOGY: This is a prospective observational study done at a tertiary care hospital- Government Maternity Hospital (GMH), Tirupati, Andhra Pradesh, India. 200 antenatal women attending OPD were included in the study. At 12-20weeks of gestational age, their serum samples were taken and analysed for levels of vitamin D. They were categorized into 3 different groups based on serum levels of vitamin D, followed till delivery and were observed of development of preeclampsia and gestational hypertension. The association between vitamin D deficiency and the development of preeclampsia and gestational hypertension was analyzed with chi-square test.RESULTS: At a cutoff value of 22.37, the ongoing investigation discovered that Vitamin D has a sensitivity of 85.06 percent and a specificity of 38.05 percent to predict preeclampsia Based on the findings of the current study, we conclude that vitamin D deficiency is associated with the development of preeclampsia and gestational hypertension.